Efficient alcoholysis of furfuryl alcohol to n‐butyl levulinate catalyzed by 5‐sulfosalicylic acid. Issue 7 (18th February 2021) - Zhao, Wenguang; Ding, Hui; Tian, Yi; Xu, Qiong; Liu, Xianxiang
Abstract: It is urgent to study the utilization of biomass energy to solve the environmental problems caused by the excessive use of fossil fuels. In this study, a rapid and efficient route for the conversion of furfuryl alcohol (FA) into n ‐butyl levulinate (BL) has been catalyzed by 5‐sulfosalicylic acid. The nearly complete conversion of FA and a considerable 99.7% selectivity of BL are obtained under the optimal conditions. Based on the experimental results, a possible mechanism for the alcoholysis of FA is proposed. The present study provided a promising way for alkyl levulinates synthesis over economical and environmentally benign catalysts. Abstract : Efficient conversion of furfuryl alcohol to n ‐butyl levulinate was experimentally studied using 5‐sulfosalicylic acid as catalysts under mild conditions, where the highest yield of 99.3% was obtained when it was employed at 118°C after 10 hr. This approach is green, simple to handle, commercially available starting materials, as well as it does not require hazardous organic solvents, thereby providing an economic, safe, and environmentally friendly route to biomass utilization.